A Case Study Of High-Temperature Corrosion In Rotary Cement Kilns - J. H. Potgieter (The Southern African Institute of Mining and Metallurgy, 2004)
This paper describes two cases of corrosion that occurred in dry-process, rotary, cement-clinker kilns. In the case of the kiln with five pre-heater stages, the attack occurred primarily from sulphates that probably originated in the raw feed and fuel being used in the plant and that penetrated the refractory lining. The corrosion was similar to ash-deposit corrosion often observed in steam boilers. In the second case the plant consisted of a long dry kiln with a single pre-heater fitted to the feed-end. In this case the corrosion could be ascribed to alkali chloride penetration through the refractory-brick lining and subsequent hot corrosion of the kiln shell.